Evolutionary game approach on fixed-mobile market - Nariaki Ikematsu (International Telecommunications Society (ITS), 2017)
Lotka-Volterra equations which equivalent to the replicator equation in evolutionary game theory under mathematical dynamic ecosystem model will provide the new basic behavior of network services. The FTTH-DSL market in Japan shifted from the co-existence model of horizontal market to the Winner-Takes-All model of FTTH. This model also shows that the fixed-mobile market in Thai and Japan have the model of the bi-stable model. This report also submits some data and materials to start discussing the new future infrastructure. The parameters of Lotka-Volterra equations are also dynamic. If parameter is constant the market does not have any innovation. It means that the survival-of-the-fittest world does not have any innovation.
Keywords: 330; Evolutionary game; Lotka-Volterra equations; fixed-mobile market